Prevalence and morphology of middle mesial canal in mandibular first molars in an Indian sub-population: A cone-beam computed tomographic analysis - Rajendra P Bharatiya; Urvashi M Ujariya; Anjali K Kothari; Viraj Yogesh Shah; Malhar Hemantbhai Naik (Wolters Kluwer Medknow Publications, 2024)
Aim: The aim of this study was to check for the prevalence and morphology of middle mesial (MM) canals in mandibular first molars in an Indian population divided as per the different zones of the country using cone-beam computed tomography (CBCT) scans. Methods: A total of 452 CBCT scans were selected according to the inclusion and exclusion criteria on December 2021. The scans were obtained from five different zones of the country with 80-100 scans selected from each zone. They were checked in an axial view to see for the presence of a MM canal (MMC) and if present, were confirmed in a coronal view. Results: Of the 452 scans viewed, 39 showed the presence of MMCs (8.6%). Bilateral presence was seen in 8 scans (1.8%). Hence, overall, 47 molars out of 904 examined showed the presence of MMCs. Thus, the tooth prevalence rate for the presence of MMC was 5.2%. Seventy percent of teeth presenting with MMCs showed two apical exits. Males showed more prevalence when compared to the female population (10.25% vs. 6.88%, P < 0.05). Furthermore, with increasing age, there was a consistent decrease in the incidence of MMCs (P < 0.05). Conclusion: Overall, the prevalence of MMCs in an Indian sub-population is 8.6%. Although on a lower range compared to other population, careful exploration is necessary to avoid missing the MMC which might lead to failure of treatment. Age and gender are also found as the important factors that influence the presence of a MMC.